Control interno a las cuentas por cobrar en el departamento de tesorería del gobierno autónomo descentralizado municipal del cantón Montalvo durante el periodo 2020-2021. - Muñoz Poveda, Jhonny Lixander (2022)
The present case study that is generated develops the analysis of internal control within the Autonomous Decentralized Municipal Government of Montalvo Canton, through the study of accounts receivable that are controlled and managed by the Treasury Department, in which a series of problems related to their daily activity, such as the collection of various property taxes, the necessary permits for operation and municipal rates, in order to satisfy citizens with the services offered, where this situation is related to singularities within the past due portfolio of the institution, as a cause of the lack of impact of the policies that the company maintains internally to promote that the debts that had been generated could be canceled, achieving an impact on the culture of payment of people, and contributing to the GAD to the generation of better activities that allow the achievement of works for the benefit of citizens. As applied methodology, historical methods can be highlighted, as well as descriptive methodology; In the same way, there is the use of methodological strategies and the analysis of correlation methodologies that generate generalized results on the facts that have been studied. As results and conclusion of the study, a diagnosis was generated on the collection procedures linked to the financial information provided by the entity, where it is reflected that the largest debts presented are generated based on the payments of Urban and Rural Properties.